Perancangan Sistem Informasi Jemaat Berbasis Web Di Gki Pulomas - Duwi Cahya Putri Buani; Yohanes Christofer Lodewico Abineno (LPPM Universitas Bina Sarana Informatika, 2022)
The design of a data processing information system is currently much needed. By designing a data processing information system, the community, especially the congregation and administrators in the Indonesian Christian Church (GKI) Pulomas Jakarta can be facilitated in the process of data processing and information provision quickly, accurately and accurately, so as to achieve efficiency and effectiveness of church work. In this research, the author uses various methods of writing, including Data Collection Techniques, Software Development Methods, System Development Model design. Create an information system in the processing of church data that should be able to improve the performance of the ministry and be able to provide fast and accurate information. So that it can help the process of church member data collection service and can be a means in conveying information to church members. registration of marriage blessings, registration of sidi, registration of lending of worship facilities and infrastructure as well as download of member charter documents, and news about church activities.